Analysis of Psychosocial Adjustment in the Family During Confinement: Problems and Habits of Children and Youth and Parental Stress and Resilience - Andrés-Romero, Magdalena P.; Flujas-Contreras, Juan M.; Fernández-Torres, Mercedes; Gómez-Becerra, Inmaculada; Sánchez-López, Pilar (Frontiers in Psychology, 2021)
The COVID-19 health crisis has led to a dramatic change in dynamics and habits of families, which may be a factor involved in the development and maintenance of problems and difficulties in children. The aim of this study is to explore the relationships between parental stress levels and problems in childhood and adolescence, considering parental resilience and changes in childhood habits due to confinement. The sample is comprised of 883 parents of children and adolescents between 3 and 18 years of age. Parental stress levels, parental resilience competencies, changes in habits, and emotional, behavioral, or peer relationship symptoms of the children during confinement were assessed. The results show a higher prevalence of emotional symptoms in primary school children and behavioral problems in children under 3 years of age. These difficulties increase significantly along the confinement period. Changes are observed in social relationships and in sleep conciliation in children. Families show a moderate level of parental stress, decreasing as the child's age increases. Overall, the level of parental resilience is high, as well as showing more resilience as children get older. The time of confinement accentuates the perception of parents about the psychological difficulties of their children and parental stress, as well as a decrease in resilience. These difficulties are reduced when the parent has resilience competencies. These results indicate the importance of parental competencies for keeping family routines that maintain the psychological adjustment of the child population.